The Role of Ecotourism in Reducing Poverty and Unemployment: A Mixed Method Approach - Xaba, Fikile; Adanlawo, Eyitayo Francis; Nkomo, Nomusa Yolanda (E-Journal of Tourism; Volume 11 Number 1 (March 2024)DO - 10.24922/eot.v11i1.114082, 2024)
Ecotourism is perceived as a promising initiative capable of poverty alleviation and job creation. This study investigated whether ecotourism helps to alleviate poverty and unemployment in relatively underdeveloped areas such as the UMkhanyakude district municipality. The study used a parallel, convergent research design comprising qualitative and quantitative research applications. Both random and purposive sampling techniques were used to select a sample of 204. In selecting respondents for the quantitative dimension, two types of databases obtained from each of the local municipalities were used. The first database comprised community registers, and the second included a list of companies registered with the municipality’s supply chain or procurement unit. Specifically, the criteria used to select participants included expertise, understanding of ecotourism programme implementation processes, skills, and proximity to ecotourism projects. Four (n = 4) officials and four (n = 4) program managers, for a total of eight, were selected from each of the four local municipalities. This resulted in a combined purposive sample of 32 participants (8 x 4 = 32) for the interviews. The Statistical Package for the Social Sciences (SPSS) was employed to analyse quantitative data. The qualitative data were processed through the ATLAS TI application. From the results, it can be deduced that, to a greater extent, ecotourism is contributing towards the reduction of poverty and unemployment in UMkhanyakude District Municipality. Based on the results, it can be concluded that ecotourism has the potential to reduce poverty and unemployment in rural communities in line with the dimensions of sustainable development goals. Benchmarking activities that focus on community roles and responsibilities, awareness-building strategies at the community level, stakeholder consultation and involvement, and capacity-building programmes are recommended.